On new Milne-type inequalities for fractional integrals - Hüseyin Budak; Pınar Kösem; Hasan Kara (Journal of Inequalities and Applications, 2023)
Abstract In this study, fractional versions of Milne-type inequalities are investigated for differentiable convex functions. We present Milne-type inequalities for bounded functions, Lipschitz functions, functions of bounded variation, etc., found in the literature. New results are established in the area of inequalities. This article is the first to study Milne-type inequalities for fractional integrals.